The recent decline in employment dynamics - Henry R. Hyatt; James Spletzer (Institute for the Study of Labor (IZA), 2013)
In recent years, the rate at which workers and businesses exchange jobs has declined in the United States. Between 1998 and 2010, rates of job creation, job destruction, hiring, and separation declined dramatically, and the rate of job-to-job flows fell by about half. Little is known about the nature and extent of these changes, and even less about their causes and implications. In this paper, we document and attempt to explain the recent decline in employment dynamics. Our empirical work relies on the four leading datasets of quarterly employment dynamics in the United States - the Longitudinal Employer-Household Dynamics (LEHD), the Business Employment Dynamics (BED), the Job Openings and Labor Turnover Survey (JOLTS), and the Current Population Survey (CPS). We find that changes in the composition of the labor force and of employers explain relatively little of the decline. Exploiting some identities that relate the different measures to each other, we find that job creation and destruction could explain as much of a third of the decline in hires and separations, while job-to-job flows may explain more of the decline. We end our paper with a discussion of different possible explanations and their relative merits.
Keywords: E24; J63; 330; hires; separations; job creation; job destruction; job-to-job flows